Rhythm: Contrasting the implications of audiation and notation - Gordon, Edwin E. (Chicago GIA, 2009)
This important book provides a thorough framework for examining rhythm what it is and how it should best be understood. Written by one of the great music thinkers and educators of our time, Edwin E. Gordon, this book will change the way you approach rhythm. This Second Edition includes expanded sections on movement, improvisation, and curriculum development. This edition also incorporates new research on audiation and several new rhythm syllables. Dr. Gordon believes that rhythm is far more than a series of note values: rhythm is truly multidimensional, and all its components need to be explored if one is to truly understand rhythm. In many cases music notation is a poor way to study rhythm, according to Dr. Gordon. This book covers topics such as: The definition of rhythm Audiation The meaning of tempo Movement Rhythm solfege Notation Usual and unusual meters Improvisation and many other related subjects Rhythm: Contrasting the Implications of Audiation and Notation is essential reading for musicologists, music history specialists, music educators, and music theorists. It is a major contribution to our understanding of rhythm, which Dr. Gordon describes as "the soul and sustenance of music."